Impact of Medial Meniscotibial Ligament Disruption Compared to Peripheral Medial Meniscal Tear on Knee Biomechanics - Smith, Patrick A.; Humpherys, Joseph L.; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2020)
Medial meniscotibial ligament (MTL) lesions may go unrecognized and untreated and have detrimental impact on knee biomechanics and joint pathology. Therefore, this study was designed to compare the biomechanical impact of midbody MTL disruption to corresponding peripheral medial meniscal (PMM) tears in anterior cruciate ligament (ACL) intact and ACL-deficient cadaveric knees. Cadaveric knees (n = 12; 6 matched pairs) were tested for laxity and ACL strain under anterior, valgus, and external rotation loading at 0, 30, and 90 degree of flexion. Knees were randomly assigned to ACL-intact (n = 6) or ACL-deficient (n = 6) groups. Large midbody MTL disruption or corresponding PMM tears were created (n = 3/group) and knees retested. PMM tears were repaired arthroscopically with inside-out suturing, and MTL lesions were repaired with suture anchors via an open approach. Knees were retested after repair. Biomechanical testing data were compared for statistically significant differences. Large MTL and PMM lesions were associated with significant increases in ACL strain, anterior laxity at 0, 30, and 90 degrees (p = 0.006), valgus laxity (p = 0.0012), and external rotation laxity (p = 0.0003) compared with intact knees. Repair of each lesion restored knee stability and reduced ACL strain to intact levels. In ACL-deficient knees, there was significantly increased anterior, valgus, and external rotation laxity compared with the ACL-intact state and MTL and PMM lesions further increased laxity at all angles. However, differences were not statistically significant and repair of meniscal lesions alone did not restore stability to ACL-deficient knees. These results highlight the need to recognize medial MTL injury and perform an appropriate repair procedure to restore knee stability and protect against excessive ACL strain.
Keywords: medial meniscus; meniscotibial ligament disruption; anterior cruciate ligament; biomechanics